Investigation on Seismic Response of Long-Span Special Steel Truss Cable-Stayed Bridge - Yong Zeng; Xueqin Li; Yutong Zeng (Advances in Civil Engineering)
Due to the small self-weight of the steel truss cable-stayed bridge with a single tower and a single cable plane, the torsional stiffness and wind stability of the structure are reduced. The arrangement of the deck type makes the mechanical properties of the cable-stayed bridge more complicated while reducing the cost and increasing the aesthetics. The effects of structural parameter variations and traveling wave effects on the seismic response of this steel truss cable-stayed bridge with a single tower and a single cable plane were investigated by the nonlinear time-history analysis method and nonuniform seismic analysis method. The results show that the displacement of the floating system under seismic action is larger than the other three systems, but its internal force is significantly smaller than the other three systems. The spectral characteristics and the duration of ground shaking have a greater influence on the maximum bending moment values corresponding to the height of the cable tower and the maximum axial force values of the main girder bars corresponding to the length of the bridge under earthquake action. The effect of steel truss girder stiffness parameter variations on structural internal forces of bridges and the effect of traveling wave effects on structural displacements of bridges in specific apparent wave velocity intervals do not exist universally.